Antioxidant activity of fruiting body extracts from Pycnoporus sanguineus mushroom - Tuong, Tran Duc; Chu, Duong Xuan; Dieu, Bui Thi Minh (Vietnam Journal of Science and Technology, 2020)
The objective of the this study is to provide an in vitro evidence for the potential antioxidant activity of the ethanolic and aqueous extracts from fruiting bodies of Pycnoporus sanguineus mushroom via DPPH free radical scavenging and lipid peroxidation inhibition assays. DPPH free radical and lipid peroxidation inhibitory activities of ethanolic and aqueous extracts from fruiting bodies of P. sanguineus were examined in a dose-response manner. Ascorbic acid and trolox were was used as a positive control for these assays and the results showed that the ethanolic extract of P. sanguineus possessed strong inhibitory activity on DPPH free radical and lipid peroxidation with IC50 values of 196.68 and 975.84 μg/mL, respectively. The aqueous extract also exhibited moderate activity against DPPH free radical and lipid peroxidation with IC50 values of 322.03 and 1311.24 μg/mL, respectively. Which was signiﬁcantly lower than that of ascorbic acid and trolox with IC50 values of 55.00 and 886.68 μg/mL, respectively. The degree of DPPH free radical and lipid peroxidation inhibition was correlated with the dose of inhibitors. Based on the obtained results, the P. sanguineus mushroom possesses high potential in antioxidant activity and could be a potential source of natural antioxidants in food and pharmaceutical applications.